3x-1=(x+2)

Simple and best practice solution for 3x-1=(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-1=(x+2) equation:


Simplifying
3x + -1 = (x + 2)

Reorder the terms:
-1 + 3x = (x + 2)

Reorder the terms:
-1 + 3x = (2 + x)

Remove parenthesis around (2 + x)
-1 + 3x = 2 + x

Solving
-1 + 3x = 2 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1 + 3x + -1x = 2 + x + -1x

Combine like terms: 3x + -1x = 2x
-1 + 2x = 2 + x + -1x

Combine like terms: x + -1x = 0
-1 + 2x = 2 + 0
-1 + 2x = 2

Add '1' to each side of the equation.
-1 + 1 + 2x = 2 + 1

Combine like terms: -1 + 1 = 0
0 + 2x = 2 + 1
2x = 2 + 1

Combine like terms: 2 + 1 = 3
2x = 3

Divide each side by '2'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| -6x/-6=6/-6 | | y=10-4/3x | | 2/13x=4 | | -7(x-2)=5(x+2) | | -8+6(5-8x)=166 | | Y+1=6(x+4) | | -7x-12=x | | -5(-5m+7)-8m=-171 | | 7(7n+6)=91 | | 2x^2+5x=5+3x-2x^2 | | N+.11=2n | | 2x+8i=6-(2y)I | | 5x-4=-2+(2x+1) | | -8(x+6)=-112 | | 2(-6n+1)=-94 | | -16=4(a-3) | | 3/8-1/6= | | 6a+4-9a=10-a | | 6x-3y=-72 | | -8(3-8k)=104 | | -2x+7x+30=15 | | 5x-31=4x-10 | | 5x-3q=4x-10 | | 6h+5=-30-h | | 8x^6+5x^3+1=0 | | 1/8x-y=7 | | (3a^2+5a-4)-(3a^2-4a+1)=4a+15 | | 5(3-2n)=85 | | 9-2x-9-16x=14x-7-4x-11 | | 19x+-9x+-11=19 | | 3g+26=g+10 | | 4(4x-3)=100 |

Equations solver categories